Techno-economic evaluation of organic solvent nanofiltration : recovering dewaxing solvent from lube-oil - Dorrington, Bella Ann (Stellenbosch : Stellenbosch University., 2020)
Thesis (MEng)--Stellenbosch University, 2020.